Chronic kidney disease risk prediction scores assessment and development in Mexican adult population - Colli, Victor A.; González-Rocha, Alejandra; Canales, David; Hernández-Alcáraz, Cesar; Pedroza, Andrea; Pérez-Chan, Manuel; Barquera, Simón; Denova-Gutierrez, Edgar (Frontiers in Medicine, 2022)
Background: Chronic kidney disease (CKD) is a major public health problem, which had considerable growth in prevalence and mortality in recent years. CKD screening at primary care is crucial for the implementation of prevention strategies. The aims of this study were to assess CKD risk prediction scores and develop a risk prediction score in the Mexican adult population. Methods: With data from the Mexican National Health and Nutrition Survey 2016 were included 3463 participants ≥20 years old. CKD was defined as reduced renal function and/or the presence of albuminuria. Results: We developed the laboratory model included sex, age, body mass index, fast plasma glucose, glomerular filtration rate, systolic blood pressure, and triglycerides, as did the office model, except for the age variable. The area under the curve (AUC) was 0.78 for laboratory model, and 0.79 in office model for Mexican adult population. Age, female gender, presence of diabetes and hypertension, elevated systolic and diastolic blood pressure, serum and urinary creatinine, and higher HbA1c were significantly associated with the prevalent chronic kidney disease. Nine predictive models of CKD risk were evaluated with a representative sample of the Mexican adult population, their AUC was between 0.74 to 0.78. Conclusions: The CKD risk predictive model designed satisfactorily predicts using simple and common variables in primary medical care. This model could have multiple benefits, such as the identification of the population at risk and prevention of CKD.